“Level of Caregivers Burden among Family Members of Mentally Ill Patients Visiting Psychiatric Outpatient Department” - Miss. Shejal Mote; Mr. Vinay Sawant; Miss. Shruti More; Miss. Sanjana Salunkhe; Miss. Sayali Kumbhar; Mr. Vansh Bansode; Mr. Suraj Jadhav; Mr. Vinayak Yadav; Dr. Praveen Subravgoudar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives: Mental health is a vital possession that needs to be cherished, promoted, and conserved. According to the WHO, around 450 million people worldwide suffer from mental or behavioral disorders. In India, approximately 20% of the population suffers from psychiatric or mental disorders. Caregivers play a crucial role in caring for mentally ill patients, but they often face significant emotional, physical, and financial burdens. The researcher aims to assess the level of caregiver burden among family members of mentally ill patients visiting the psychiatric outpatient department (OPD) at Dr. D.Y. Patil Medical College Hospital and Medical Research Institute, Kolhapur. The study seeks to understand the impact of care giving on family members and identify ways to support them. Objectives: The present study is aimed that to assess the level of caregivers burden among family members of mentally ill patients visiting psychiatric OPD at Dr. D. Y. Patil Medical College Hospital and Medical Research Institute, Kolhapur. The objectives are as follows, 1. To assess the level of care givers burden among family member of mentally ill patients. 2. To find the association between level of care givers burden with selected demographic variables among family member of mentally ill patients. Methods: A quantitative descriptive survey approach was used, with a non-experimental descriptive research design. A sample of 60 family members of mentally ill patients was selected using non-probability purposive sampling technique. The Zarit Caregivers Burden Scale was used to collect the data on level of caregivers burden among family member of mentally ill patients. Result: The majority of respondents (46.66%) experienced a mild to moderate level of burden. 30%, had no or minimal burden, while 20% experienced moderate to severe burden. Only 3.33% of individuals experienced a severe level of burden. Significant associations were found between caregiver burden and age, residence, and education. Interpretation and conclusion: The study concludes that the Level of Caregiver’s Burden among Family Member of Mentally Ill Patients Visiting Psychiatric OPD at Dr. D. Y. Patil Medical College Hospital and Medical Research Institute at Kolhapur, isthe majority of respondents (46.66%) experienced a mild to moderate level of burden. There is a need for healthcare professionals to assess and address caregiver burden among family members of mentally ill patients. The findings have implications for nursing practice, education, administration, and research, as well as general education in schools and colleges. Recommendations for future studies and interventions to support caregivers are also provided.